الطقوس المتعلقة بدفن الميت وتأثيرها على المجتمع الأفغاني ; دراسة فى ضوء مقاصد الشريعة: Funeral Rites and Their Impact on Afghan Society; A Study in the light of Objectives of Sharia (Al-Aasar, 2025)
This research explores the funeral rites observed in Afghan society, examining their religious, social, and cultural roots, as well as their positive and negative effects. It discusses common practices such as burying the deceased in a coffin, covering women during burial, and having female deceased lowered into the grave by their male relatives. The study reveals that some of these practices have a basis in Islamic law and are expressions of respect and modesty, such as covering the body during burial, while others like the use of coffins without necessity may lead to wastefulness or imitation of non-Islamic customs. The research warns that if such rituals are not balanced by sound religious principles, they can evolve into innovations or impose unnecessary social pressure when viewed as obligatory. It emphasizes the importance of balancing religious compliance with beneficial social customs, avoiding excess or unfounded practices. The study concludes that community awareness and proper religious education are essential to refining these practices in a way that aligns with Islamic objectives and preserves human dignity.